Analisis Maslahah terhadap Tradisi Ajun Arah dalam Adat Kerinci: Perspektif Hukum Islam - Lagus, Wegestin; Azwar, Zainal (Fakultas Syariah IAI Muhammadiyah Bima, 2025)
Ajun Arah is a tradition of customary law in the Kerinci community that regulates the procedure for establishing a house through permits and briefings from traditional stakeholders. This tradition plays a role in maintaining social order, strengthening family values, and ensuring fair and orderly land use in the community. This research aims to analyze the practice of Ajun Arah from the perspective of maslahah in Islamic law and assess its relevance in the midst of modern social and legal developments. Using a qualitative-normative study employing a literature-based method, this study examines the extent to which Ajun Arah provides benefits to society and supports the main goals of Islamic sharia (maqashid sharia), especially in the protection of property (hifzh al-mal) and social order. The results of the study show that Ajun Arah can be categorized as a practice that reflects the maslahah mursalah, because it provides real benefits without contradicting sharia principles. This tradition helps prevent land ownership conflicts, strengthens indigenous social structures, and creates harmony in the community. However, along with the dynamics of land laws and regulations in Indonesia, there is a need for renewal and harmonization so that the Ajun Arah remains relevant, does not cause legal overlap, and is inclusive for all citizens. The maslahah-based approach opens up space for the preservation of this tradition in a more contextual, adaptive manner, and still based on Islamic justice values.